2019
DOI: 10.22211/cejem/109717
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Mechanical and Thermal Properties, and Impact Sensitivity of Pressed HMX-based PBX

Abstract: Article is available under the Creative Commons Attribution-Noncommercial-NoDerivs 3.0 license CC BY-NC-ND 3.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Data from Wang et al [1] showed that the higher the porosity of the explosive charge, the higher the impact sensitivity. But the research results of Li et al [2] showed that the impact sensitivity is slightly lower when the charge density is higher. Results from Liu et al [3] showed that friction sensitivity of HMX decreased when the particle size of HMX decreased; but Wang et al [4] got the opposite results for HMX.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Data from Wang et al [1] showed that the higher the porosity of the explosive charge, the higher the impact sensitivity. But the research results of Li et al [2] showed that the impact sensitivity is slightly lower when the charge density is higher. Results from Liu et al [3] showed that friction sensitivity of HMX decreased when the particle size of HMX decreased; but Wang et al [4] got the opposite results for HMX.…”
Section: Introductionmentioning
confidence: 94%
“…In practice, there are some factors influence the mechanical sensitivities of energetic materials, such as crystal type, particle size, additives, and so on. Much confused, in literature, conclusions from different authors are often different, even opposite [1][2][3][4][5][6][7] . Data from Wang et al [1] showed that the higher the porosity of the explosive charge, the higher the impact sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the interaction force between these binders and explosives is small, the contact is not close enough or the addition of binders leads to a decrease in the thermal conductivity of PBXs compared to elemental explosives. In addition, the formation of the interface will affect the thermal conductivity of the PBXs [22][23][24]. The decrease in thermal conductivity will cause the local temperature of PBXs to rise, forming a hot spot, which can cause an explosion if the energy of such a hot spot is too high [25].…”
Section: Introductionmentioning
confidence: 99%